Fazil Say’s «Shahmeran»: the metamodern paradigm of an Eastern myth in the music of a Turkish composer - Kupina, Daryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study The relevance of this study stems from the insufficient scholarly exploration of Turkish academic music, particularly its contemporary manifestations, which integrate Eastern traditions with Western compositional techniques. The musical legacy of Fazıl Say, one of the most prominent representatives of 21st-century Turkish music, showcases a unique synthesis of national identity and global musical trends, reflecting Turkey's broader cultural context as a crossroads of civilizations. The main objective of the study is to examine the stylistic features of Fazıl Say’s symphonic poem «Shahmeran» as a realization of an Eastern myth in the context of global cultural trends of modernity, particularly metamodernism as a contemporary artistic paradigm. The methodologу includes the following approaches: the biographical method (to analyze the impact of the composer’s sociocultural environment on his creativity), the genre-stylistic method (to determine the genre characteristics of the composition and its connection with the traditions of Western instrumental music), the intonational-dramaturgical method (to explore the construction of the musical narrative), as well as cultural-historical and theoretical generalization methods (to define the place of the composition within the contemporary musical discourse). Results and conclusions. The symphonic poem «Shahmeran» by Fazıl Say is analyzed through the lens of the metamodern artistic paradigm as a multilayered composition that synthesizes elements of Eastern mythology, Turkish musical traditions, and contemporary compositional techniques. The central role of the myth of Shahmeran is identified as a tool for reinterpreting cultural heritage and generating new meanings within a globalized world. Emphasis is placed on the capacity of myth to function as a dynamic cultural code, adapting to modern challenges while maintaining its connection to archetypal structures, aligning with the key characteristics of metamodernism. The preconditions for the development of Turkish academic music are outlined, and the main factors that contributed to its rapid growth in the second half of the 20th century are determined. Fazıl Say’s creative method is examined, highlighting the influence of his active career as a pianist and his overseas education. Say’s compositional style is characterized as synthetic, seamlessly integrating Western compositional techniques with the distinctiveness of national musical traditions. The genre status of «Shahmeran» is identified as ambiguous, blending elements of a single-movement symphonic poem and a cello concerto under the framework of a programmatic title. The compositional features of the work are analyzed, including its fragmentary structure and non-linear form. The role of modalintonational and rhythmic specificities in shaping its distinct Eastern modality is emphasized. The significance of oriental instruments (kudüm, waterphone) and unique performance techniques (aleatory glissandi, the use of strings as percussion, and cello timbres approximating traditional instruments) is revealed, highlighting their contribution to the creation of a distinctive sonic landscape. It is demonstrated that the composer employs methods of «new simplicity», presented through the prism of oriental intonations.